2021
DOI: 10.1111/cbdd.13827
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antifungal effects of curcumin derivatives as fungal biofilm inhibitors with fluconazole

Abstract: Lack of novel antifungal agents and severe drug resistance has led to high incidence and associated mortality of invasive fungal infections. To tackle the challenges, novel antifungal agents with anti‐resistant potency are highly desirable. Thus, derivatives of curcumin were synthesized to restore the effectiveness of fluconazole (FLC) against FLC‐resistant Candida spp. and structure‐activity relationships were then discussed. Some novel derivatives showed promising features as novel antifungal lead compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…3 Among them there are certain distinctive substances containing the 2-arylvinyl (styryl) group at various positions of a heterocycle, as well as their analogs. 4 Styrylpyrazoles, styrylpyrazolines and similarly structured substances possess antitumor, 5 antioxidative, 5 l,o ,6 antibacterial, 7 antimalarial, 8 antifungal, 9 and anti-inflammatory 10 properties, and some other types of biological activities 11 (also see the references in the review by Gomes and coworkers 4 for details). Furthermore, styrylpyrazoles have valuable photophysical abilities.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among them there are certain distinctive substances containing the 2-arylvinyl (styryl) group at various positions of a heterocycle, as well as their analogs. 4 Styrylpyrazoles, styrylpyrazolines and similarly structured substances possess antitumor, 5 antioxidative, 5 l,o ,6 antibacterial, 7 antimalarial, 8 antifungal, 9 and anti-inflammatory 10 properties, and some other types of biological activities 11 (also see the references in the review by Gomes and coworkers 4 for details). Furthermore, styrylpyrazoles have valuable photophysical abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The satisfactory performance of curcumin against Candida biofilms has led to the use of this compound for inhibiting drug-resistant strains. In this regard, Dong et al (2021) used curcumin to restore the effectiveness of fluconazole against fluconazole-resistant Candida . Curcumin alone or in combination with fluconazole suppressed biofilm formation and yeast-to-hypha morphological transition in fluconazole-resistant C. albicans .…”
Section: Curcuminmentioning
confidence: 99%
“…Furthermore, this compound combined with fluconazole disrupted membrane permeability and reduced intracellular ATPase production. The synergism of curcumin and fluconazole has introduced this compound as a new therapeutic agent against drug-resistant Candida strains ( Dong et al, 2021 ). However, there is limited data on the curcumin and antifungals interactions; thus, further studies are required.…”
Section: Curcuminmentioning
confidence: 99%
“…Several phytochemicals have been found to potentially inhibit biofilm formation and, in combination with FLC, exhibit synergistic effects against C. albicans biofilms ( 9 ). For example, Dong et al found that a combination of curcumin derivatives and FLC showed synergistic antifungal activity against C. albicans biofilm formation ( 10 ). Pseudolaric acid A (PAA) is a diterpenoid extracted from a traditional Chinese medicine, the root bark of Pseudolarix kaempferi .…”
Section: Introductionmentioning
confidence: 99%